Linking Theories of Motivation, Game Mechanics, and Public Deliberation to Design an Online System for Participatory Budgeting. (February 2021) - Gastil, John; Broghammer, Michael
Existing systems for online civic engagement and public consultation need a better architecture if they are to realize the aspirations of deliberative democracy. To improve the design of such systems, we develop an empirical model of online civic engagement that connects common game mechanics to four key democratic processes and outcomes—inclusion, deliberative engagement, sound and influential public input, and long-term civic impacts. We then link game mechanics and deliberation with theories of motivation to show how these mechanics can leverage people's drives to fulfill basic needs, forge social connections, and gain status. To illustrate our model in more concrete terms, we show how game mechanics could motivate both participants and policymakers in an online participatory budgeting system. We conclude by describing a multi-stage experimental approach to testing this model within an existing system of online participatory budgeting.